1998
DOI: 10.1139/z98-089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary specialization in two sympatric populations of killer whales (Orcinus orca) in coastal British Columbia and adjacent waters

Abstract: Two forms of killer whale (Orcinus orca), resident and transient, occur sympatrically in coastal waters of British Columbia, Washington State, and southeastern Alaska. The two forms do not mix, and differ in seasonal distribution, social structure, and behaviour. These distinctions have been attributed to apparent differences in diet, although no comprehensive comparative analysis of the diets of the two forms had been undertaken. Here we present such an analysis, based on field observations of predation and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
490
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(528 citation statements)
references
References 39 publications
(61 reference statements)
13
490
2
Order By: Relevance
“…Ecotypes may also exhibit differences in social structure, morphology, behavior and vocal signatures (see for review de Bruyn et al (2013)). In the North Pacific, the resident and transient ecotypes occupy largely sympatric distribution ranges (Ford et al, 2000), but specialize on very different prey resources (fish and marine mammals, respectively; Ford et al, 1998;Krahn et al, 2007), are genetically differentiated (Hoelzel et al, 1998(Hoelzel et al, , 2002(Hoelzel et al, , 2007, and exhibit different social organization (Ford et al, 2000), mating systems (Pilot et al, 2010) and vocal behavior (Yurk et al, 2002;Deecke et al, 2005). Less is known about the 'offshore' ecotype, however, our data indicate that we need to consider their differentiation in sympatry as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ecotypes may also exhibit differences in social structure, morphology, behavior and vocal signatures (see for review de Bruyn et al (2013)). In the North Pacific, the resident and transient ecotypes occupy largely sympatric distribution ranges (Ford et al, 2000), but specialize on very different prey resources (fish and marine mammals, respectively; Ford et al, 1998;Krahn et al, 2007), are genetically differentiated (Hoelzel et al, 1998(Hoelzel et al, , 2002(Hoelzel et al, , 2007, and exhibit different social organization (Ford et al, 2000), mating systems (Pilot et al, 2010) and vocal behavior (Yurk et al, 2002;Deecke et al, 2005). Less is known about the 'offshore' ecotype, however, our data indicate that we need to consider their differentiation in sympatry as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several studies where differences were found in feeding habits of populations of the same species living in distinct habitats: killer whales (Orcinus orca) in the Pacific Northwest on the border between the US and Canada (Ford et al 1998); sea lions (Eumetopias jubatus) in Alaska (Kurle & Gudmundson 2007); and dolphin species in Australia (Owen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the feeding ecology of specific species is considered essential in order to implement effective conservation measures (Owen et al 2011). Franciscana individuals from a separate population found in the nearshore area, located outside of the bay, were also included in the analysis in order to check for variation in feeding strategies of the same species in relation to habitat differences (Ford et al 1998). The diet of these populations was characterized to complement the findings of a recent study on their feeding strategies, which analyzed the stomach contents of specimens collected in Babitonga Bay (Cremer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by stable social groups, populationspecific foraging strategies and vocal repertoires that are likely to be transmitted through learning. Their feeding behaviors include hunting fishes, cephalopods, sea turtles, sea birds, mustelids, pinnipeds and cetaceans (e.g., Martinez & Klinghammer, 1970;Christensen, 1978;Smith et al, 1981;Hoelzel, 1991;Jefferson et al, 1991;Baird et al, 1992;Similä & Ugarte, 1993;Matkin & Saulitis, 1994;Baird & Dill, 1995;Baird & Dill, 1996;Fertl et al, 1996;Similä et al, 1996;Ford et al, 1998;Baird & Whitehead, 2000;Ford & Ellis, 2006;Simon et al, 2006). The diversity of hunting strategies parallels the diversity of prey on which they feed.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%